2016
DOI: 10.1016/j.ultsonch.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic agitation on adhesion strength of micro electroforming Ni layer on Cu substrate

Abstract: Micro electroforming is an important technology, which is widely used for fabricating micro metal devices in MEMS. The micro metal devices have the problem of poor adhesion strength, which has dramatically influenced the dimensional accuracy of the devices and seriously limited the development of the micro electroforming technology. In order to improve the adhesion strength, ultrasonic agitation method is applied during the micro electroforming process in this paper. To explore the effect of the ultrasonic agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This is due to the effect of microbubbles explosion from the supercritical CO 2 affects nucleation growth during the electrodeposition. Notably, the observed diffraction pattern in US-SC-CO 2 -15 W cm −2 displays the most significant full width at half maximum (FWHM), which indicated that ultrasonic agitation would lead to the smallest grain size [16] , [23] , [24] . Similar to the previous reports, the grain sizes are calculated from the Scherrer equation [38] , [39] , [40] , [41] , [42] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the effect of microbubbles explosion from the supercritical CO 2 affects nucleation growth during the electrodeposition. Notably, the observed diffraction pattern in US-SC-CO 2 -15 W cm −2 displays the most significant full width at half maximum (FWHM), which indicated that ultrasonic agitation would lead to the smallest grain size [16] , [23] , [24] . Similar to the previous reports, the grain sizes are calculated from the Scherrer equation [38] , [39] , [40] , [41] , [42] .…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, ultrasonic-assisted electrodeposition has been widely used to improve the quality of electrodeposited materials [22] , [23] , [24] . It is due to the fact of high energy from the ultrasonic irradiation that creates cavitation effects such as mass transport processes, acoustic streaming, surface activation, and micro jetting formation [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, owing to the cavitation and the micro jet effects, the ultrasonic assisted method was widely used in the electroplating field. The beneficial effects include producing nano grained hydroxyapatite coating, compacting the nice contact and reducing the internal stress [11][12][13]. Generally, the properties of the electroplating layer can be refined by the ultrasonic assisted method [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…To electroform a multilayered microstructure successfully, the adhesion between adjacent layers is critical, which signi cantly affects the mechanical performance, reliability and serve time of the micro device [6][7]. Weak interface bonding can even lead to the warpage or delamination of electrodeposited layers and nally result in the fabrication failure.…”
Section: Introductionmentioning
confidence: 99%